ADVANCING DOMESTIC TOURISM IN UZBEKISTAN: CHALLENGES, OPPORTUNITIES, AND POLICY INTERVENTIONS - Jasmina, Sabirova (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Uzbekistan's domestic tourism sector remains underdeveloped despite its rich cultural and natural resources, primarily due to infrastructure deficiencies, high travel costs, and limited policy support. This study addresses the knowledge gap by employing a mixed-methods approach, integrating qualitative stakeholder interviews and quantitative surveys to identify barriers and growth opportunities. Method: This study addresses the knowledge gap by employing a mixed-methods approach, integrating qualitative stakeholder interviews and quantitative surveys to identify barriers and growth opportunities. Results: Findings reveal that improving infrastructure, reducing travel costs, and enhancing marketing strategies are critical for domestic tourism expansion. Results highlight the need for government intervention through targeted policies and investments in sustainable tourism models. Novelty: The study provides practical recommendations to strengthen Uzbekistan’s tourism sector, fostering economic growth and regional development.